Structural design and parameter determination for fluted-roller fertilizer applicator - Zeng, Shan; Tan, Yipeng; Wang, Yu; Luo, Xiwen; Yao, Lamei; Huang, Denpang; Mo, Zewen (International Journal of Agricultural and Biological Engineering, 2020)
The instability of the motion layer of fertilizer particle influences the precision and the accuracy of the amount of fertilizer application in the working process of fluted-roller fertilizer applicator. The characteristics of the motion layer were investigated, and a systematic scheme was proposed for designing the structures of fertilizer-filling cavity, fertilizer-filling surface and fertilizer-delivery cavity. The key parameters of the structure were studied by discrete element method. It was figured out that to ensure the smooth operation of fertilizer applicator, the fertilizer-filling angle was 105°, fertilizer-contact angle should be large than 100°, and the fertilizer-resistance angle should be smaller than 35°. Moreover, the stability of fertilizer motion morphology was investigated to verify the design. The results showed that when the roll rotational speed was larger than 120 deg/s, compared with the conventional design the CV of the amount of fertilizer application was reduced from 1.5%-3.5% to 0.5%-1.0%, and the accuracy of the fertilizer discharge was improved with the square of the correlation coefficient between the amount of fertilizer application and the roll rotational speed was larger than 0.999. It was deduced from the results that the precision and accuracy of the amount of fertilizer application are improved via eliminating the driving layer and enhancing the stable filling and conveying of the forced layer. Keywords: fertilizer applicator, fluted-roller, precision fertilization, structural design, structural parameters DOI: 10.25165/j.ijabe.20201302.4999 Citation: Zeng S, Tan Y P, Wang Y, Luo X W, Yao L M, Huang D P, et al. Structural design and parameter determination for fluted-roller fertilizer applicator. Int J Agric & Biol Eng, 2020; 13(2): 101–110.